Age-related appearance of a CMV-specific high-avidity CD8(+ )T cell clonotype which does not occur in young adults - Schwanninger, Angelika (BioMed Central, 2008)
Old age is associated with characteristic changes of the immune system contributing to higher incidence and severity of many infectious diseases. Particularly within the T cell compartment latent infection with human Cytomegalovirus (CMV) is contributing to and accelerating immunosenescence. However, latent CMV infection and reactivation usually does not cause overt symptoms in immunocompetent elderly persons indicating immunological control of disease. Little is still known about the clonal composition of CMV-specific T cell responses in donors of different age. We therefore analyzed CD8(+ )T cells specific for an immunodominant pp65-derived nonamer-peptide (NLVPMVATV; CMV(NLV)) in different age-groups. Independent of donor age CMV(NLV)-specific CD8(+ )T cells preferentially use the V beta family 8. This family has monoclonal expansions in the majority of donors after stimulation of CD8(+ )T cells with the peptide. By sequencing the CDR3 region of the T cell receptor we demonstrated that CMV(NLV)-specific, BV8(+ )CD8(+ )T cells share the conserved CDR3-sequence motif SANYGYT in donors of all age groups. Interestingly, a second conserved clonotype with the CDR3-sequence motif SVNEAF appears in middle-aged and elderly donors. This clonotype is absent in young individuals. The age-related clonotype SVNEAF binds to the pMHC-complex with higher avidity than the clonotype SANYGYT, which is predominant in young adults. The dominance of this high avidity clonotype may explain the lack of overt CMV-disease in old age.